Practitioner research at doctoral level : developing coherent research methodologies - Drake, Pat (Routledge, 2011)
The authors of this book explore in detail the challenges faced by doctoral researchers conducting practitioner research today. As a guide to this often neglected aspect of doctoral research, the authors of this book explore in detail the challenges faced by doctoral researchers conducting practitioner research today.